オーロラ・オーストラリス ニヨル ユソウ ト オーストラリア ノ ケーシーキチ オヨビ マッコーリートウ キチ ノ シセツ - 石沢, 賢二; イシザワ, ケンジ; 北川, 弘光; キタガワ, ヒロミツ; Ishizawa, Kenji; Kitagawa, Hiromitsu (2007)
P(論文) オーストラリア南極観測隊でチャーターしている「オーロラ・オーストラリス」の性能及び荷役作業を調査した.著者の一人(石沢)は,2005/2006年第5次航海に参加し,この船舶調査の他にケーシー基地及びマッコーリー島基地の施設についても調査した.この調査は,2008/2009シーズンに行う昭和基地への人員・物資輸送を,この砕氷船で実施する際の可能性を探るために実施された.その結果,この砕氷船は,南極への輸送に使用できる性能を有していることが確かめられた.また,訪問した両基地の施設運営は,効率良く行われており,その情報は日本南極観測隊の運営に役立つと考えられる. The authors visited the Australian Antarctic vessel "Aurora Australis"at Hobart and investigated her navigation performance and cargo operation. One of the authors (Kenji Ishizawa) participated in her fifth voyage and visited Casey and Macquarie Island Stations from March to April 2006. One of the purposes of the investigation was to examine the feasibility of her being chartered for transport of personnel and cargo to Syowa Station in the 2008/2009 season. The second purpose was to investigate the facilities at Casey and Macquarie Island Stations. The knowledge gained through our investigations confirmed that through careful operation and accumulated experience, the vessel could be used for transport of personnel and cargo for the JARE (Japanese Antarctic Research Expedition) to Syowa Station in the 2008/2009 season. The facilities at these two stations were operated effectively. These Australian facilities can provide much useful information for the further development of JARE. departmental bulletin paper